Ceramic tile with humidifying function and preparation method thereof
By using raw materials such as pumice powder, volcanic mud and toner in ceramic tiles, and combining low-temperature firing technology, the problem of insufficient mechanical strength of ceramic tiles is solved, and ceramic tiles with high mechanical strength and good humidity regulation function are achieved, improving the overall performance of the product.
Patent Information
- Application Number
- CN202411610970.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-28
AI Technical Summary
While ensuring the humidity control function, existing wet-regulating ceramic tiles have insufficient mechanical strength and are prone to deformation or cracking during drying, affecting the performance of the product.
Pumice powder, volcanic mud and carbon powder are used as the main moisture-regulating raw materials, and glass powder, sodium feldspar and borax, as well as ceramic basic raw materials kaolin and ceramic solid waste are added. Through low-temperature firing technology, ceramic tiles with high mechanical strength and good humidity-regulating function are formed.
The high mechanical strength and good humidity regulation function of ceramic tiles are achieved, deformation and cracking are avoided, and the overall performance of the product is improved. The moisture absorption and humidity release amount are significantly improved in 24 hours, and the flexural strength reaches 17.9-19.8MPa.
Smart Images

Figure BDA0005130886540000021 
Figure BDA0005130886540000041 
Figure BDA0005130886540000042
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building ceramics, and in particular relates to a ceramic tile with a humidity regulating function and a preparation method thereof. Background Art
[0002] With the development of economy and society, people are increasingly dependent on indoor environment, and they spend more and more time indoors. According to statistics from relevant institutions, urban residents in my country spend more than 80% of their time indoors every day, and the quality of indoor environment directly affects people's quality of life. Indoor air humidity is an important reference value for measuring the quality of indoor living environment, which is directly related to human physical and mental health, object storage, heating energy consumption, etc. High indoor humidity can easily breed mold, cause materials to absorb water and deform and accelerate damage, and accelerate the corrosion of metal materials. Low indoor humidity can easily generate static electricity, objects are prone to brittleness and accelerated cracking, etc.
[0003] At present, the main methods for indoor humidity regulation are active humidity control methods such as air conditioners, dehumidifiers and humidifiers, but these methods have high energy consumption. Therefore, the development and application of humidity control materials with good humidity control functions have important social value and significance for improving the living environment, object preservation, and ecological sustainable development.
[0004] In the prior art, the most studied humidity control material is a porous structure material with a high specific surface area, which can be used as a passive humidity control material to prepare humidity control functional bricks. When the indoor humidity is high, the porous structure can preserve moisture through physical adsorption and reduce the indoor humidity; when the indoor humidity is low, the porous structure can release moisture into the air, thereby increasing the indoor humidity and keeping the indoor humidity within a comfortable range for the human body. However, in order to prevent the high-temperature firing environment from destroying the porous structure of the humidity control functional bricks, the firing temperature is generally controlled within a lower range (700-850℃). Because if the firing temperature is too high, the pore structure of the raw material will be reduced, and the humidity control function cannot be achieved; and low-temperature firing is not conducive to the mechanical strength of the ceramic product.
[0005] Therefore, there is an urgent need to develop a ceramic tile that has high mechanical strength while ensuring its good humidity regulating function, so as to better meet application requirements. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a ceramic tile with humidity control function and a preparation method thereof, the ceramic tile not only has good humidity control function, but also has high mechanical strength, and the product surface has no deformation and cracking.
[0007] In order to solve the above technical problems, the first aspect of the present invention provides a ceramic tile, wherein the raw material components of the ceramic tile include, by weight:
[0008]
[0009] The ceramic tile of the present invention uses pumice powder, volcanic mud and carbon powder as main humidity control raw materials, and adds low-temperature flux raw materials such as glass powder, albite and borax, as well as ceramic basic raw materials kaolin and ceramic solid waste. After low-temperature firing, the humidity control function of the ceramic tile is realized, the mechanical strength of the product is improved, and the deformation and cracking of the product are prevented.
[0010] Specifically, pumice powder has a rich porous structure and is a natural humidity-controlling material. When fired at a relatively low temperature, the porous structure can be preserved relatively intact, thereby preserving a good function of regulating air humidity. That is, when the air humidity is high, the porous structure absorbs moisture from the air into the pore structure through adsorption; when the air humidity is low, the porous structure can release the adsorbed moisture through desorption, thereby achieving the function of regulating air humidity. However, since the main component of pumice is silicon dioxide, which is a lean raw material, the green body must meet a relatively high moisture content during molding, and the high moisture content green body is prone to deformation and cracking due to the evaporation of water during the drying process. Therefore, the amount of pumice added should not be too high, which is not conducive to the humidity-control function of the product.
[0011] In view of the above-mentioned problems existing in pumice, the present invention introduces volcanic mud and carbon powder into the formula at the same time. Among them: volcanic mud is a porous material with a high specific surface area, and also has good water retention and air humidity regulating functions. At the same time, volcanic mud is a clay raw material, which has strong adhesion when it comes into contact with water, and can effectively improve the strength of the green body, thereby effectively solving the deformation and cracking of pumice during the molding process. Carbon powder reacts with oxygen to generate CO2 during the firing process, which will form abundant open through holes inside the ceramic tile. These open through holes are a beneficial supplement to the porous structure of pumice powder and volcanic mud, increase the connection between the internal pore structure of the product and the outside, greatly improve the utilization rate of the internal pore structure, and further enhance the humidity regulating function of the ceramic tile.
[0012] In some embodiments of the present invention, the particle size of the pumice powder is 500-1200 mesh. Fine-grained pumice powder has a high specific surface area, which is more conducive to the moisture-adjusting function of the product.
[0013] In some embodiments of the present invention, the chemical composition of the volcanic mud includes, by weight percentage: 49-58% SiO2, 17-27% Al2O3, 1-4% CaO, 0-2% MgO, 1-3% K2O, 1-2% Na2O, 5-8% Fe2O3 and 3-5% loss on ignition.
[0014] Specifically, the main components of volcanic mud are SiO2, Al2O3, Fe2O3 and CaO, which are the basic raw materials for ceramic tiles. In addition, the high specific surface area and plasticity of volcanic mud not only help to improve the humidity regulating function of the product, but also effectively avoid deformation and cracking of ceramic tiles during the drying process.
[0015] In some embodiments of the present invention, the melting temperature of the glass powder is 600-700°C.
[0016] Specifically, the present invention selects low-temperature melting glass powder with a suitable melting temperature, which can form a sufficient melt during the firing process, thereby improving the mechanical strength of the ceramic tile without affecting the humidity control function of the product due to the clogging of the porous structure by the glass melt.
[0017] In some embodiments of the present invention, the glass powder has a particle size of 500-1500 mesh.
[0018] In some embodiments of the present invention, the particle size of the carbon powder is 500-1000 mesh.
[0019] In some embodiments of the present invention, the ceramic solid waste includes polishing waste residue and / or porcelain tile waste residue. The polishing waste residue of the present invention is the waste residue generated during the polishing process of ceramic tiles, and the porcelain tile waste residue is the waste residue generated during the production process of porcelain tiles, such as the excess powder generated during spray drying, powder screening, aging, storage, and press molding. Both polishing waste residue and porcelain tile waste residue are recyclable ceramic raw materials and will not have a negative effect on the performance of the product.
[0020] The second aspect of the present invention provides a method for preparing the above-mentioned ceramic tile, comprising the following steps:
[0021] (1) Mixing various raw materials for preparing ceramic tiles, wet grinding, and spray granulation to obtain powder;
[0022] (2) Pressing the powder into a shape, drying it, and firing it in a kiln to obtain the ceramic brick.
[0023] In some embodiments of the present invention, in step (1), the temperature of the spray granulation is 450-550°C.
[0024] In some embodiments of the present invention, in step (1), the moisture content of the powder is 5-9wt%.
[0025] In some embodiments of the present invention, in step (2), the sintering temperature is 700-850°C.
[0026] In some embodiments of the present invention, in step (2), the sintering period is 60-80 minutes.
[0027] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0028] (1) The present invention uses pumice powder, volcanic mud and carbon powder as the main humidity-control raw materials, glass powder, sodium feldspar and borax as low-temperature flux raw materials, and adds ceramic base raw materials kaolin and ceramic solid waste. After low-temperature firing, a high-strength humidity-control ceramic tile is prepared, and the deformation and cracking of the product are prevented. Among them: pumice powder has a rich porous structure. When fired at a lower temperature, the porous structure can be retained relatively intact, thereby preserving a good function of regulating air humidity. As a porous material with a high specific surface area, volcanic mud also has good water retention and air humidity regulation functions; at the same time, volcanic mud has strong adhesion when it meets water, which effectively improves the strength of the ceramic tile body and avoids the deformation and cracking of pumice during the molding process. During the firing process, carbon powder forms a rich open through hole inside the ceramic tile, which increases the connection between the internal pore structure of the product and the outside, greatly improves the utilization rate of the internal pore structure, and further enhances the humidity regulation function of the ceramic tile.
[0029] (2) The present invention optimizes and rationally compound various raw materials to prepare ceramic tiles with good humidity control function and mechanical strength, and the product has no deformation and cracking, and achieves a 24-hour moisture absorption of 325-342g / m 2 , moisture release is 299-309g / m 2 , the flexural strength reaches 17.9-19.8MPa. DETAILED DESCRIPTION
[0030] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0031] Example 1
[0032] A ceramic tile, the raw material components of which include, by weight:
[0033]
[0034] Wherein: the particle size of the pumice powder is 800 mesh; the chemical composition of the volcanic mud, by weight percentage, includes: 55% SiO2, 25% Al2O3, 3% CaO, 1.5% MgO, 2.5% K2O, 2% Na2O, 7% Fe2O3 and 4% loss on ignition; the melting temperature of the glass powder is 600°C, and the particle size of the glass powder is 1000 mesh; the particle size of the carbon powder is 800 mesh.
[0035] A method for preparing a ceramic tile comprises the following steps:
[0036] (1) pumice powder, volcanic mud, albite, clay, ceramic waste, glass powder, borax and carbon powder were weighed according to mass ratio, wet-grinded, and spray-granulated at 450° C. to obtain a powder with a moisture content of 7 wt %;
[0037] (2) The powder obtained in step (1) is evenly distributed in a mold, pressed into shape, dried, and then fired in a kiln, wherein the firing temperature is 750° C. and the firing cycle is 60 minutes, to obtain the ceramic tile of this embodiment.
[0038] Example 2
[0039] A ceramic tile, the raw material components of which include, by weight:
[0040]
[0041]
[0042] Wherein: the particle size of the pumice powder is 900 mesh; the chemical composition of the volcanic mud, by weight percentage, includes: 55% SiO2, 25% Al2O3, 3% CaO, 1.5% MgO, 2.5% K2O, 2% Na2O, 7% Fe2O3 and 4% loss on ignition; the melting temperature of the glass powder is 600°C, and the particle size of the glass powder is 800 mesh; the particle size of the carbon powder is 800 mesh.
[0043] A method for preparing a ceramic tile comprises the following steps:
[0044] (1) pumice powder, volcanic mud, albite, clay, ceramic waste, glass powder, borax and carbon powder were weighed according to mass ratio, wet-grinded, and spray-granulated at 450° C. to obtain a powder with a moisture content of 7 wt %;
[0045] (2) The powder obtained in step (1) is evenly distributed in a mold, pressed into shape, dried, and then fired in a kiln, wherein the firing temperature is 750° C. and the firing cycle is 60 minutes, to obtain the ceramic tile of this embodiment.
[0046] Example 3
[0047] A ceramic tile, the raw material components of which include, by weight:
[0048]
[0049] Wherein: the particle size of the pumice powder is 500-1200 mesh; the chemical composition of the volcanic mud, by weight percentage, includes: 56% SiO2, 25% Al2O3, 3% CaO, 1.5% MgO, 2.5% K2O, 1% Na2O, 7% Fe2O3 and 4% loss on ignition; the melting temperature of the glass powder is 650°C, and the particle size of the glass powder is 1000 mesh; the particle size of the carbon powder is 900 mesh.
[0050] A method for preparing a ceramic tile comprises the following steps:
[0051] (1) pumice powder, volcanic mud, albite, clay, ceramic waste, glass powder, borax and carbon powder were weighed according to mass ratio, wet-grinded, and spray-granulated at 450° C. to obtain a powder with a moisture content of 7 wt %;
[0052] (2) The powder obtained in step (1) is evenly distributed in a mold, pressed into shape, dried, and then fired in a kiln, wherein the firing temperature is 750° C. and the firing cycle is 60 minutes, to obtain the ceramic tile of this embodiment.
[0053] Example 4
[0054] A ceramic tile, the raw material components of which include, by weight:
[0055]
[0056] Wherein: the particle size of the pumice powder is 1000 mesh; the chemical composition of the volcanic mud, by weight percentage, includes: 54% SiO2, 26% Al2O3, 3% CaO, 1.5% MgO, 2.5% K2O, 2% Na2O, 7% Fe2O3 and 4% loss on ignition; the melting temperature of the glass powder is 650°C, and the particle size of the glass powder is 1500 mesh; the particle size of the carbon powder is 1000 mesh.
[0057] A method for preparing a ceramic tile comprises the following steps:
[0058] (1) pumice powder, volcanic mud, albite, clay, ceramic waste, glass powder, borax and carbon powder were weighed according to mass ratio, wet-grinded, and spray-granulated at 450° C. to obtain a powder with a moisture content of 7 wt %;
[0059] (2) The powder obtained in step (1) is evenly distributed in a mold, pressed into shape, dried, and then fired in a kiln, wherein the firing temperature is 750° C. and the firing cycle is 60 minutes, to obtain the ceramic tile of this embodiment.
[0060] Comparative Example 1
[0061] A ceramic tile, the raw material components of which include, by weight:
[0062]
[0063] Wherein: the particle size of the pumice powder is 800 mesh; the chemical composition of the volcanic mud includes, by weight percentage: 55% SiO2, 25% Al2O3, 3% CaO, 1.5% MgO, 2.5% K2O, 2% Na2O, 7% Fe2O3 and 4% ignition loss; the particle size of the carbon powder is 800 mesh.
[0064] A method for preparing a ceramic tile comprises the following steps:
[0065] (1) pumice powder, volcanic mud, albite, clay, ceramic waste, borax and carbon powder were weighed according to mass ratio, wet-grinded, and spray-granulated at 450° C. to obtain a powder with a moisture content of 7 wt %;
[0066] (2) The powder obtained in step (1) is evenly distributed in a mold, pressed into shape, dried, and then fired in a kiln, wherein the firing temperature is 750° C. and the firing cycle is 60 min, to obtain the ceramic brick of this comparative example.
[0067] The difference between Comparative Example 1 and Example 1 is that the raw material components of the ceramic tile are different, and the ceramic raw material components of Comparative Example 1 do not contain glass powder.
[0068] Comparative Example 2
[0069] A ceramic tile, the raw material components of which include, by weight:
[0070]
[0071] Wherein: the particle size of the pumice powder is 800 mesh; the chemical composition of the volcanic mud, by weight percentage, includes: 55% SiO2, 25% Al2O3, 3% CaO, 1.5% MgO, 2.5% K2O, 2% Na2O, 7% Fe2O3 and 4% loss on ignition; the melting temperature of the glass powder is 600°C, and the particle size of the glass powder is 1000 mesh.
[0072] A method for preparing a ceramic tile comprises the following steps:
[0073] (1) pumice powder, volcanic mud, albite, clay, ceramic waste, glass powder and borax are weighed according to mass ratio, wet-grinded, and spray-granulated at 450° C. to obtain a powder with a moisture content of 7 wt %;
[0074] (2) The powder obtained in step (1) is evenly distributed in a mold, pressed into shape, dried, and then fired in a kiln, wherein the firing temperature is 750° C. and the firing cycle is 60 minutes, to obtain the ceramic tile of this embodiment.
[0075] The difference between Comparative Example 2 and Example 1 is that the raw material components of the ceramic tiles are different, and the ceramic raw material components of Comparative Example 2 do not contain carbon powder.
[0076] Comparative Example 3
[0077] The only difference between Comparative Example 3 and Example 1 is that the raw material component of the ceramic brick in Comparative Example 3 uses an equal amount of rice husk powder to replace the carbon powder in Example 1.
[0078] Comparative Example 4
[0079] The difference between Comparative Example 4 and Example 1 is that the raw material components of the ceramic brick of Comparative Example 4 use an equal amount of kaolin to replace the volcanic mud in Example 1. That is, the raw material components of the ceramic brick of Comparative Example 5 include, by weight:
[0080]
[0081]
[0082] Performance Testing
[0083] The ceramic tile samples prepared in Examples 1-4 and Comparative Examples 1-4 were tested for humidity control performance, flexural strength, deformation and cracking. Among them: the humidity control performance was tested in accordance with the standard JC-T 2002-2009 "Test Method for Moisture Absorption and Desorption Performance of Building Materials", wherein: the moisture absorption refers to the moisture absorption of the sample in 24 hours when the ambient temperature is 23°C and the ambient humidity is 95%; the moisture release refers to the moisture release of the sample in 24 hours when the ambient temperature is 23°C and the ambient humidity is 35%. The flexural strength was tested in accordance with the standard GB / T3810.4-2016 "Test Method for Ceramic Tiles", and the deformation and cracking were tested in accordance with the standard GB / T 3810.2-2016 "Test Method for Ceramic Tiles-Part 2: Inspection of Dimensions and Surface Quality", and the test results are shown in Table 1.
[0084] Table 1:
[0085]
[0086] As shown in Table 1, the ceramic tile samples prepared in Examples 1-3 all have good humidity control function and mechanical strength, and the 24-hour moisture absorption capacity is 325-342 g / m 2 , moisture release is 299-309g / m 2 The flexural strength can reach 17.9-19.8MPa; and the product surface is smooth without obvious cracks.
[0087] Compared with Example 1, since glass powder is not added to the raw material components of the ceramic tile, the flexural strength of the sample is significantly reduced, which proves that the glass powder has a good effect of improving the mechanical strength of the sample.
[0088] Comparative Examples 2-3, compared with Example 1, have significantly decreased humidity control functions of the samples due to the fact that no carbon powder was added to the raw material components of the ceramic tiles or the pore-forming agent rice husk powder was used to replace the carbon powder. This proves that carbon powder has a good effect on promoting the humidity control function of pumice and volcanic mud; and although rice husk powder also has a pore-forming effect, it has no effect on promoting the humidity control function of ceramic tiles due to the different through-hole structure formed by carbon powder during the firing process.
[0089] Compared with Example 1, since common clay raw material kaolin is used to replace volcanic mud, not only the humidity regulating function is reduced, but also the flatness of the sample cannot meet the standard requirement (<0.5mm), and obvious cracks appear on the surface of the sample.
[0090] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A ceramic tile, characterized in that: The raw material components of the ceramic brick include, by weight:
2. The ceramic tile according to claim 1, characterized in that: The particle size of the pumice powder is 500-1200 meshes.
3. The ceramic tile according to claim 1, characterized in that: The chemical composition of the volcanic mud includes, by weight percentage, 49-58% SiO2, 17-27% Al2O3, 1-4% CaO, 0-2% MgO, 1-3% K2O, 1-2% Na2O, 5-8% Fe2O3 and 3-5% ignition loss.
4. The ceramic tile according to claim 1, characterized in that: The melting temperature of the glass powder is 600-700°C.
5. The ceramic tile according to claim 1 or 4, characterized in that: The particle size of the glass powder is 500-1500 meshes.
6. The ceramic tile according to claim 1, characterized in that: The particle size of the carbon powder is 500-1000 meshes.
7. The ceramic tile according to claim 1, characterized in that: The ceramic solid waste includes polishing waste residue and / or porcelain tile waste residue.
8. A method for preparing a ceramic tile according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Mixing various raw materials for preparing ceramic tiles, wet grinding, and spray granulation to obtain powder; (2) Pressing the powder into a shape, drying it, and firing it in a kiln to obtain the ceramic brick.
9. The method for preparing a ceramic tile according to claim 8, characterized in that: In step (1), the spray granulation temperature is 450-550° C.; and / or the moisture content of the powder is 5-9wt%.
10. The method for preparing a ceramic tile according to claim 8, characterized in that: In step (2), the sintering temperature is 700-850° C.; and / or the sintering period is 60-80 min.
Citation Information
Cited By
Porous ceramic tile with humidifying function and preparation method thereof
CN121135473A
Porous ceramic tile with humidity regulating function and method for manufacturing the same
CN121135473B